Case reports with literature review of an aneurysmal bone cyst in the maxilla and mandible of two juvenile dogs - Adley, Colin; Volker, Mary Krakowski (Frontiers in Veterinary Science, 2025)
This report identifies two cases of juvenile dogs with an aneurysmal bone cyst (ABC). The first case describes an ABC in the left rostral mandible, and the second case describes an ABC in the right maxilla. ABCs are typically identified in juvenile or young animals and have been reported in a variety of species. An ABC results from the intraosseous expansion of soft or immature bone and is more appropriately identified as a pseudocyst due to the absence of an epithelial lining. An ABC is most likely believed to be caused by trauma, which contributes to the formation of an expansile, blood-filled lesion encased with immature, proliferative bone. The classic presentation is an osteolytic, cavitated lesion in the metaphysis region of long bones. Both diagnostic imaging and histopathology are required for the diagnosis of an ABC, with differential diagnoses being fibrosarcoma, osteolytic osteosarcoma, osteoblastic or giant cell tumor, the unilocular membrane-lined simple bone cyst, ameloblastoma, fibro-odontoma, and papillary squamous cell carcinoma. In human medicine, ABCs are found in the head and neck region in 2–12% of reported cases, with 60–70% of the cases occurring in the jaws. Aneurysmal bone cysts in the maxillofacial region of the dog are a rare finding in veterinary medicine and are currently without confirmed etiopathogenesis. The following case reports describe an ABC in the left rostral mandible of a 7-month-old dog treated with complete excision and an ABC in the right maxilla of a 12-week-old dog treated with incisional biopsy and curettage that showed resolution of right facial swelling before being lost to follow-up. These cases and literature review add to the paucity of veterinary literature regarding aneurysmal bone cysts in dogs and provide case descriptions and treatment recommendations for this rare juvenile lesion.